2017
DOI: 10.1021/acs.jpca.7b02040
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of N2O5 with Salty and Surfactant-Coated Glycerol: Interfacial Conversion of Br to Br2 Mediated by Alkylammonium Cations

Abstract: Gas-liquid scattering and product-yield experiments are used to investigate reactions of NO with glycerol containing Br and surfactant ions. NO oxidizes Br to Br for every solution tested: 2.7 M NaBr, 0.03 M tetrahexylammonium bromide (THABr), 0.03 M THABr + 0.5 M NaBr, 0.03 M THABr + 0.5 M NaCl, 0.03 M THABr + 0.01 M sodium dodecyl sulfate (SDS), and 0.01 M cetyltrimethylammonium bromide (CTABr). NO also reacts with glycerol itself to produce mono- and dinitroglycerin. Surface tension measurements indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 82 publications
2
41
0
Order By: Relevance
“…While one recent study has shown that cationic surfactants can enhance the rate of N 2 O 5 bulk‐phase reaction by facilitating surface reactions (Shaloski et al, ), the majority of previous laboratory studies have found that the presence of organics suppresses γ (N 2 O 5 ) relative to pure inorganic salts. The magnitude of suppression, however, is strongly dependent on the organic composition (e.g., Griffiths et al, ; Gross et al, ), particle phase state (e.g., Thornton et al, ), and the presence of surfactants (e.g., Cosman et al, , and references therein), which are controlled by factors such as RH, temperature, and molecular structure and composition.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…While one recent study has shown that cationic surfactants can enhance the rate of N 2 O 5 bulk‐phase reaction by facilitating surface reactions (Shaloski et al, ), the majority of previous laboratory studies have found that the presence of organics suppresses γ (N 2 O 5 ) relative to pure inorganic salts. The magnitude of suppression, however, is strongly dependent on the organic composition (e.g., Griffiths et al, ; Gross et al, ), particle phase state (e.g., Thornton et al, ), and the presence of surfactants (e.g., Cosman et al, , and references therein), which are controlled by factors such as RH, temperature, and molecular structure and composition.…”
Section: Discussionmentioning
confidence: 68%
“…Treating organics as a coating with the other three parameterizations improves the median percent difference but cannot reproduce the full range in WINTER values. Both underprediction and overprediction could result from a number of factors including incorrect estimation of the coating thickness, bulk‐phase diffusion and solubility rates, or an enhancement from organics by facilitating surface reactions (Shaloski et al, ). Similar to WINTER, results from three previous field studies found that the simplified resistor framework generally underpredicted γ (N 2 O 5 ), likely due to an overprediction of the organic suppression effect (Morgan et al, ; Phillips et al, ), but improved agreement relative to the inorganic‐only parameterizations (Chang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Separate studies provide insights into the mechanism of dissolution and reaction. [39,45,46]. In all three cases, the product DCl or Br 2 evaporates in a Maxwellian distribution at the temperature of the liquid.…”
Section: Maxwellian Evaporation and A Two-step Model For Solvationmentioning
confidence: 90%
“…During 30 years of observation, we have monitored the vacuum evaporation of liquids such as glycerol, ethylene glycol, alkanes and aromatics, fluorinated ethers, and water from sulfuric acid and pure and salty water itself [39][40][41][42][43]. [39,40,42,[44][45][46][47][48]. We observed Maxwellian speed distributions in every case (except when the vapor pressure is so high that the gas expands supersonically [41,49]).…”
Section: Maxwellian Evaporation and A Two-step Model For Solvationmentioning
confidence: 99%
“…TBA exhibits also a strong ion-pairing capacity, which makes TBA ions important in various areas of chemistry, e.g., in phase-transfer catalysis, where relatively hydrophobic cations are used for precipitating large anions . Several studies have addressed the interfacial properties of TBA containing iodide solutions (including mixtures with bromide) with VUV photoemission. Also molecular beam scattering experiments of N 2 O 5 interacting with a liquid jet containing tetraalkylammonium surfactants indicated interactions between the positively charged surfactant and reactants or products, also depending on the solvent. , Overall, the details of how charged surfactant ions affect the halide ions, their reactivity, and potentially also reaction products have remained open.…”
Section: Introductionmentioning
confidence: 99%